PERAN DISPORA PROVINSI RIAU DALAM PEMBINAAN ATLET PELAJAR MELALUI PROGRAM PUSAT PENGEMBANGAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) TAHUN 2015-2017 - Permana, Jaka; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The PPLP program is an education and training center for talented student athletes which is a manifestation of the system of organizing training to achieve the desired results, increasing performance in national and international sports. This research is motivated by the role in fostering the athletes of PPLP students in Riau Province in 2015-2017 which is carried out by Dispora but in its implementation experiences various problems, such as the achievements and quality of athletes which are declining every year. The purpose of this study is to analyze the problems that occur in the implementation of the program that causes a decrease in athlete achievement. The method used in this research is descriptive method with the type of qualitative research. The type of research data is primary data and secondary data. Data collection techniques in this study were documentation and interviews. The data analysis technique used is descriptive qualitative data analysis. The results showed that the role of Dispora in coaching PPLP athletes in Riau Province was not running optimally. This can be seen from the not yet effective planning of activity programs. There are inhibiting factors both in terms of internal and external; provision of facilities and infrastructure that are not yet efficient and do not create coordination between the same level institutions. The right solution to overcome the problems in the PPLP program management process is to create a neater and more effective program planning and produce policies that can improve coordination between each institution concerned. Keywords: Planning of sports activities, maintenance of sports facilities and dormitories, organizing try outs and competitions, achievements